Strengthening capacities for evidence-based policy planning and implementation in Africa: IFPRI’s support to CAADP in 2013 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
This report highlights achievements made in 2013 by IFPRI and its partners in support of the CAADP implementation agenda through ReSAKSS, the AGRODEP Modeling Consortium, and analytical work on agricultural growth and investment options.